Comparative Study on Red Mud Modified Intumescent Coating - NORDIN, AFIF AIMAN (IRC, 2016)
Red mud is a waste residue resulting from extraction of bauxite by Bayer process. This study investigated the fire resistance of the red mud intumescent coating for steel structures. Red mud is a worldwide environmental problem, and many authorities are trying to find an economic solution for its beneficial application or/and safe disposal. The purchased red mud already undergoes sea water treatment in order to reduce the pH-value. The coating was modified in term of coating formula. All the sample was prepared on the 100 mm x 100 mm x 3 mm and leave the coating to be rest for 48 hours before immerse in to the sea water. The formula for each intumescent coating was different in term of mass and present of additive material such as hydrochloric acid, titanate pyrophosphate and oxalic acid. This additive material was added into coating formula for modification of red mud intumescent coating. Moisture index and formation of char for the red mud modified intumescent coatings were analyzed. EDX analysis was used to obtained the element present in the formed char.